DESAIN TATA KELOLA REKAM MEDIS BERBASIS TEKNOLOGI INFORMASI GUNA MENUNJANG PELAPORAN PELAYANAN RAWAT INAP - Dafiq Farhan Nurdias; Fauzan Mahar Dhika Rahmat; Falaah Abdussalaam; Irda Sari (Media Bina Ilmiah, 2023)
The processing and calculation of data in one of the hospitals in the city of Bandung is still manually and not computerized, such as the processing of daily inpatient census data and the processing of Barber Johnson indicator data which has the parameters BOR, LOS, TOI, BTO which have possibilities high human errors. Therefore  inpatient efficiency system is created that can facilitate officers.. This study aims to design an integrated system. The design of this data processing system uses the advanced v-model method which known as the Verification and Validation mode. While making the application itself using the C# programming language with MySQL for database processing. This application was tested using Blackbox Testing with the results as expected and running well so that this application makes the processing and reporting generation more effective and efficient as well as easy to use and understand